2021
DOI: 10.1155/2021/6697659
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Range of Nursing Skills Used to Provide Social Support for Mothers of Preterm Infants in Neonatal Intensive Care

Abstract: Background. Hospitalization of preterm infants in neonatal intensive care units (NICUs) is a stressful experience for parents. Iranian NICUs do not have specified levels of care, nor do they integrate supportive methods of parent support such as family-centered care approaches. This study investigated the range and types of neonatal nursing support, as perceived by mothers of preterm infants, and its association with mothers’ satisfaction with infant care in the NICU. Methods. This is a descriptive, correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…A cross-sectional study showed that mothers perceived nursing support in terms of affirmational, concrete aid, and affectional in an acceptable level and the perceived nursing support was significantly associated with mothers’ satisfaction with preterm infant care in the NICU. 47 In another study, the amount of support provided by nurses in the NICU with single-family rooms (SFRs) was compared with the amount of support provided by nurses in an open bay (OB) NICU. The results showed that the presence of mothers in the SFR group had positive consequences including enhancement of the median presence of mothers with their infants, increase of their participation in decision-making and medical rounds, and increase of the nursing support including guidance, information, and emotional support.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A cross-sectional study showed that mothers perceived nursing support in terms of affirmational, concrete aid, and affectional in an acceptable level and the perceived nursing support was significantly associated with mothers’ satisfaction with preterm infant care in the NICU. 47 In another study, the amount of support provided by nurses in the NICU with single-family rooms (SFRs) was compared with the amount of support provided by nurses in an open bay (OB) NICU. The results showed that the presence of mothers in the SFR group had positive consequences including enhancement of the median presence of mothers with their infants, increase of their participation in decision-making and medical rounds, and increase of the nursing support including guidance, information, and emotional support.…”
Section: Resultsmentioning
confidence: 99%
“…All of them were published in English from 2012 to 2021. Six studies were from Iran, 31,35,42,44,45,47 two from South Korea, 34,41 two from Norway, 28,39 two from the United States, 29,33 one was from Canada, 32 one from Japan, 38 one from Denmark, 30 one from Jordan, 46 one from France, 40 one from Italy, 36 one from Sweden, 43 and one from Turkey. 37…”
Section: Resultsmentioning
confidence: 99%
“…Implication for Practice. One of the important roles of nurses during patient care is to identify patients' anxiety and apply the most efective method to improve their wellbeing [72,73]. Also, nurses have the responsibility to consider the safety of the anxiety relieving method in patient care.…”
Section: Discussionmentioning
confidence: 99%
“…(2) greater maternal satisfaction with neonatal nurses' care for infants in Iran (Eskandari et al, 2021). A study of patients with breast cancer in 83 German hospitals (Lubasch et al, 2021) found higher patient-perceived social support from nurses in institutions with better process organisation (i.e., superior nurse-physician communication and more coordination between different units).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…The literature related specifically to social support from nurses is rather scarce. Increased social support from nurses has been shown to be associated with (1) improved adherence to therapy among patients with tuberculosis in the Philippines (Baniqued et al, 2020) and (2) greater maternal satisfaction with neonatal nurses' care for infants in Iran (Eskandari et al, 2021). A study of patients with breast cancer in 83 German hospitals (Lubasch et al, 2021) found higher patient‐perceived social support from nurses in institutions with better process organisation (i.e., superior nurse‐physician communication and more coordination between different units).…”
Section: Introductionmentioning
confidence: 99%